2007
DOI: 10.1128/ec.00308-06
|View full text |Cite
|
Sign up to set email alerts
|

The 29-Kilodalton Thiol-Dependent Peroxidase of Entamoeba histolytica Is a Factor Involved in Pathogenesis and Survival of the Parasite during Oxidative Stress

Abstract: The 29-kDa surface antigen (thiol-dependent peroxidase; Eh29) of Entamoeba histolytica exhibits peroxidative and protective antioxidant activities. During tissue invasion, the trophozoites are exposed to oxidative stress and need to deal with highly toxic reactive oxygen species (ROS). In this investigation, attempts have been made to understand the role of the 29-kDa peroxidase gene in parasite survival and pathogenesis. Inhibition of eh29 gene expression by antisense RNA technology has shown approximately 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Our positive results could be due to the longer annexin V reaction period used. Our lab had previously shown that after 6 h exposure to oxidative stress, E. histolytica shows annexin-positive staining (Sen et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our positive results could be due to the longer annexin V reaction period used. Our lab had previously shown that after 6 h exposure to oxidative stress, E. histolytica shows annexin-positive staining (Sen et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, direct divalent reduction of O 2 to H 2 O 2 is catalysed by an NADPH : flavin oxidoreductase (Bruchhaus et al, 1998). Catalase and glutathione reductase systems are absent in E. histolytica (Sen et al, 2007), but the H 2 O 2 generated by both pathways can be further transformed to H 2 O by the action of peroxiredoxin (eh29) (Bruchhaus et al, 1997). The mRNA level of SOD and eh29 was found to decrease gradually with the increase in duration of exposure to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…During tissue invasion, the trophozoites are exposed to oxidative stress and need to deal with highly toxic reactive oxygen species (Coombs et al 2004;Sen et al 2007). Toxic molecules such as superoxide (O 2 · − ) and hydrogen peroxide (H 2 O 2 ) can alter membrane properties and disrupt membrane-bound proteins and biological macromolecules, leading to cell death (Sen et al 2007). Therefore T. vaginalis has to maintain its redox homeostasis for survival.…”
Section: Defense and Stress-related Proteinsmentioning
confidence: 99%
“…The cytotoxicity data are a significant finding, as the relative difficulty in manipulating gene expression in E. histolytica has limited the ability to associate particular genes with pathogenicity. To date, only a few amebic genes have been genetically shown to be involved in cytotoxicity (3,11,16,25,29,43,47).…”
Section: Macfarlane and Singh Eukaryot Cellmentioning
confidence: 99%